2018
DOI: 10.1038/s41598-018-28271-7
|View full text |Cite
|
Sign up to set email alerts
|

Cognition based bTBI mechanistic criteria; a tool for preventive and therapeutic innovations

Abstract: Blast-induced traumatic brain injury has been associated with neurodegenerative and neuropsychiatric disorders. To date, although damage due to oxidative stress appears to be important, the specific mechanistic causes of such disorders remain elusive. Here, to determine the mechanical variables governing the tissue damage eventually cascading into cognitive deficits, we performed a study on the mechanics of rat brain under blast conditions. To this end, experiments were carried out to analyse and correlate pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 79 publications
(94 reference statements)
0
33
0
Order By: Relevance
“…Specifically, we have noted conspicuous microvascular damage, neuroinflammation, and increased oxidative stress in the hours and days following injury (Walls et al, 2016). Furthermore, we have discovered a significant elevation of acrolein, an α,β-unsaturated aldehyde that is both a product and catalyst of lipid peroxidation and stimulator of oxidative stress and inflammation (Garcia-Gonzalez et al, 2018;Walls et al, 2016). Finally, we have demonstrated that acrolein plays a key role in the pathogenesis of PD in a 6-OHDA injection model, highlighting the need for additional mechanistic investigations (Ambaw et al, 2018).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Specifically, we have noted conspicuous microvascular damage, neuroinflammation, and increased oxidative stress in the hours and days following injury (Walls et al, 2016). Furthermore, we have discovered a significant elevation of acrolein, an α,β-unsaturated aldehyde that is both a product and catalyst of lipid peroxidation and stimulator of oxidative stress and inflammation (Garcia-Gonzalez et al, 2018;Walls et al, 2016). Finally, we have demonstrated that acrolein plays a key role in the pathogenesis of PD in a 6-OHDA injection model, highlighting the need for additional mechanistic investigations (Ambaw et al, 2018).…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, dopaminergic neurons in the SN are known to be more susceptible to oxidative processes than dopaminergic neurons found elsewhere in the brain (Burns et al, 1983;German et al, 1988;Hung and Lee, 1998;Wang and Michaelis, 2010;Waters et al, 1987). Differential mechanical injury profiles between brain regions could also contribute, wherein the SN experiences more injurious loading conditions than the STR, as our lab's computational biomechanics work in this mb-TBI model has suggested (Garcia-Gonzalez et al, 2018). Regardless of the underlying mechanism, these data suggest differential localization and regulation of the TH protein between different brain loci, in a similar fashion to the α-syn protein, after injury.…”
Section: Disruption Of Dopaminergic Synthesis Via Dysregulation Of Tymentioning
confidence: 95%
See 1 more Smart Citation
“…The FEHM is adapted from a previous version proposed earlier by Garcia-Gonzalez et al ( 2018b ), where it was validated for cranial impacts. It accounts for the gray matter, white matter with axonal anisotropy captured from diffusion tensor imaging (DTI), cerebrospinal fluid (CSF), skull, falx, scalp, and ventricles and consists of 2,354,594 tetrahedral elements.…”
Section: Methodsmentioning
confidence: 99%
“…However, as local mechanical disturbances in the brain can lead to time-dependent systemic biological and multiphysics responses, these models are intrinsically unable to mechanistically predict functional alterations or cognitive deficits. Barring a few exceptions (Garcia-Gonzalez et al, 2018b ), very little work has focussed on correlating functional deficits, tissue damage, and mechanical features in a fully validated framework, e.g., with clinical or animal data. Even then, in most of the cases, the high cost (both in man-hour and computational) to develop, run, and analyze the underlying FEHM remains extremely impractical and not fit for direct clinical use.…”
Section: Introductionmentioning
confidence: 99%